Structural Elucidation of Trace Components Combining GC/MS, GC/IR, DFT‐Calculation and Synthesis—Salinilactones, Unprecedented Bicyclic Lactones from Salinispora Bacteria. Issue 45 (15th October 2018) - Schlawis, Christian; Kern, Simone; Kudo, Yuta; Grunenberg, Jörg; Moore, Bradley S.; Schulz, Stefan
Abstract: The analysis of volatiles released by marine Salinispora bacteria uncovered a new class of natural compounds displaying an unusual bicyclic [3.1.0]‐lactone skeleton. Although only sub‐μg quantities of the compounds were available, the combination of analytical methods, computational spectroscopy, and synthesis allowed unambiguous structural identification of the compounds, called salinilactones, without the need for isolation. Orthogonal hyphenated methods, GC/MS and solid‐phase GC/IR allowed to propose a small set of structures consistent with the data. A candidate structure was selected by comparison of DFT‐calculated IR spectra and the experimental IR‐spectrum. Synthesis confirmed the structure and absolute configuration of three bicyclic lactones, salinilactones A–C. The salinilactones are structurally closely related to the A‐factor class of compounds, autoregulators from streptomycete bacteria. They exhibited inhibitory activity against Salinispora and Streptomyces strains. Abstract : The combination of orthogonal hyphenated methods, GC/MS, gas chromatography/solid‐phase infrared spectroscopy (GC/IR), computational spectroscopy, and synthesis led to the discovery of three volatile bicyclic lactones emitted by marine Salinispora bacteria, salinilactones A–C. These unprecedented bicyclic [3.1.0]‐lactones are closely related to the A‐factor class of γ‐butyrolactone autoregulators from certain actinomycetes.